Impact of COVID-19 lockdowns on adolescent pregnancy and school dropout among secondary schoolgirls in Kenya. Issue 1 (13th January 2022) - Zulaika, Garazi; Bulbarelli, Miriam; Nyothach, Elizabeth; van Eijk, Annemieke; Mason, Linda; Fwaya, Eunice; Obor, David; Kwaro, Daniel; Wang, Duolao; Mehta, Supriya D; Phillips-Howard, Penelope A
Abstract : Introduction: Secondary school closures aimed at limiting the number of infections and deaths due to COVID-19 may have amplified the negative sexual and reproductive health (SRH) and schooling outcomes of vulnerable adolescent girls. This study aimed to measure pandemic-related effects on adolescent pregnancy and school dropout among school-going girls in Kenya. Methods: We report longitudinal findings of 910 girls in their last 2 years of secondary school. The study took place in 12 secondary day schools in rural western Kenya between 2018 and 2021. Using a causal-comparative design, we compared SRH and schooling outcomes among 403 girls who graduated after completion of their final school examinations in November 2019 pre-pandemic with 507 girls who experienced disrupted schooling due to COVID-19 and sat examinations in March 2021. Unadjusted and adjusted generalised linear mixed models were used to investigate the effect of COVID-19-related school closures and restrictions on all outcomes of interest and on incident pregnancy. Results: At study initiation, the mean age of participants was 17.2 (IQR: 16.4–17.9) for girls in the pre-COVID-19 cohort and 17.5 (IQR: 16.5–18.4) for girls in the COVID-19 cohort. Girls experiencing COVID-19 containment measures had twice the risk of falling pregnant prior to completing secondary school after adjustment for age, household wealth and orphanhood status (adjusted risk ratio (aRR)=2.11; 95% CI:1.13 to 3.95, p=0.019); three times the risk of school dropout (aRR=3.03; 95% CI: 1.55 to 5.95, p=0.001) and 3.4 times the risk of school transfer prior to examinations (aRR=3.39; 95% CI: 1.70 to 6.77, p=0.001) relative to pre-COVID-19 learners. Girls in the COVID-19 cohort were more likely to be sexually active (aRR=1.28; 95% CI: 1.09 to 1.51, p=0.002) and less likely to report their first sex as desired (aRR=0.49; 95% CI: 0.37 to 0.65, p<0.001). These girls reported increased hours of non-school-related work (3.32 hours per day vs 2.63 hours per day in the pre-COVID-19 cohort, aRR=1.92; 95% CI: 1.92 to 2.99, p=0.004). In the COVID-19 cohort, 80.5% reported worsening household economic status and COVID-19-related stress was common. Conclusion: The COVID-19 pandemic deleteriously affected the SRH of girls and amplified school transfer and dropout. Appropriate programmes and interventions that help buffer the effects of population-level emergencies on school-going adolescents are warranted. Trial registration number: NCT03051789 .